2(x+8)=9x+9-7x+7

Simple and best practice solution for 2(x+8)=9x+9-7x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+8)=9x+9-7x+7 equation:


Simplifying
2(x + 8) = 9x + 9 + -7x + 7

Reorder the terms:
2(8 + x) = 9x + 9 + -7x + 7
(8 * 2 + x * 2) = 9x + 9 + -7x + 7
(16 + 2x) = 9x + 9 + -7x + 7

Reorder the terms:
16 + 2x = 9 + 7 + 9x + -7x

Combine like terms: 9 + 7 = 16
16 + 2x = 16 + 9x + -7x

Combine like terms: 9x + -7x = 2x
16 + 2x = 16 + 2x

Add '-16' to each side of the equation.
16 + -16 + 2x = 16 + -16 + 2x

Combine like terms: 16 + -16 = 0
0 + 2x = 16 + -16 + 2x
2x = 16 + -16 + 2x

Combine like terms: 16 + -16 = 0
2x = 0 + 2x
2x = 2x

Add '-2x' to each side of the equation.
2x + -2x = 2x + -2x

Combine like terms: 2x + -2x = 0
0 = 2x + -2x

Combine like terms: 2x + -2x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| x^2-8+16=16 | | 0=x^2+0.036x-0.00693 | | (2h)+2=26 | | 20x-4y-5z+7=0 | | -6(x+2)+7=1x+6 | | 3x=5-2(2+4x) | | 3x-14y=-49 | | -6t-7= | | 6(x+2)+7=1x+6 | | 2xy^2-xy=0 | | 3x+1+3x=67 | | (x-24)+29=360 | | 15+2x=12.5x+2.5 | | 3(y+4)=12 | | 2b-10=5-3b | | 12.5x=10.5 | | -6b=-5b+10 | | 2(y-8)=20 | | 7h=4+6h | | (7(x+5)-18)+(3(x-2)+4)= | | 12.3x-9.2=3x-0.7x | | x+(x*1.08)=188000 | | 7(-3+6x)=-21 | | 2x+3=5x-4+7 | | x^4+1500x^2+1250000=0 | | x*23=33 | | 7x=3x+26 | | 8x-(3x-6)=26 | | 7(2x-1)=11x+5 | | 2a+7=-2-3 | | H=68t-8t | | (9(y+5)-18)+(3(y-3)+5)= |

Equations solver categories